Current Trends in Regulating the Legal Status of Private Military and Security Companies: Array - Cauia , Alexandr; Zacon , Corina (Journal of Danubian Studies and Research, 2021)
The presence of employees of private military and security companies in the grey zones and in military operations is a reality. The legal regulation of the status of these companies, the types and essence of the services provided, as well as the legal mechanism for prosecuting employees seriously infringing the provisions of international humanitarian law is an imperative need for the international regulatory process and a challenge for the science of international humanitarian law. This article will continue to discuss the correlation between the duties, obligations of non-state actors and their legal status in accordance with the provisions of international humanitarian law, to analyze documents and legal instruments that seek to regulate the legal capacity of military and private security companies, to investigate aspect related to the implementation of the rules described in the documents proposed by the international community.